OPTIMASI SISTEM PENCAHAYAAN RUANG KULIAH TERKAIT USAHA KONSERVASI ENERGI - Dewi, Evi Puspita (Institute of Research and Community Outreach - Petra Christian University, 2011)
The lighting system in a classroom has to be considered appropriately in designing buildings and energy managemen must also be optimized. Bad used of lighting systems can cause low productivity, comfort and also result in waste of energy. Simulation results and experimental observations with DIALux v4.9 program show that the lighting system in the classrooms of the P building in Petra Christian University has not been optimally designed with consideration and does not meet the national standard of lighting system for energy conservation in Indonesia (SNI). By rearranging the interior elements and the implementation of control systems based with the teaching time and media, the lighting systems in the interior space could be improved and also conserve energy upto 36.4%.